(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
In the application of reconnaissance, post-disaster recovery, and search and rescue operations, researchers are significantly exploring amphibious robots owing to their excellent locomotion capabilities in diverse environments. An amphibious robot needs locomotion to maneuver on irregular, uneven terrains on land and a dynamic water medium. The study presents an amphibious robot that employs a rocker-bogie mechanism with an adjustable link providing retractable and unretractable configuration suitable on terrestrial and aquatic mediums. This paper proposes an amphibious robot vehicle (ARV) unretractable mode suitable for inclined locomotion on uneven land surface and retracted mode suitable for locomotion on water. Experiment investigation demonstrates Cross hill and downhill Grade ability on inclined surfaces that stabilize the ARV preventing it from slippage and flip over. The trainability and adaptability on land. The Simulation in Ansys for flow velocity vector shows retractable wheel position significantly improves trust forces by reducing the low bow losses. An integrated paddle mechanism will be employed in future design to increase the mobility on the Water Wheel.